The closure of Palaeo-Tethys in Eastern Myanmar and Northern Thailand: New insights from zircon U–Pb and Hf isotope data - N. J. Gardiner (2018)
© 2015 International Association for Gondwana Research Two of the major granite belts of Southeast Asia are the Main Range and Eastern Province. Together, these are interpreted to represent the magmatic expression of the closure of Palaeo-Tethys during Late Palaeozoic to Early Mesozoic times. Recent geochronological and geochemical work has better delineated these belts within Peninsular Malaysia, thereby providing important constraints on the timing of Palaeo-Tethys suturing. However, the northern extension of this Palaeo-Tethyan suture is less well understood. Here we present new ion microprobe U–Pb zircon age data from northern Thailand and eastern Myanmar. Measured ages of 219 and 220 Ma from the Kyaing Tong granite imply northern extension of the Main Range Province into eastern Myanmar. The Tachileik granite in far eastern Myanmar yields an age of 266 Ma, consistent with published Eastern Province ages, and this therefore constrains the northern extension of the Palaeo-Tethys suture in eastern Myanmar. We further discuss how this suture may extend northwards into Yunnan. A Late Cretaceous age (70 Ma) measured in Thailand represents later magmatic activity, and is similar to published magmatic ages from central Myanmar. This younger magmatism is interpreted to be related to the subduction of Neo-Tethys prior to India–Asia collision. Further, we present new laser ablation zircon Hf isotope data from eastern Myanmar which suggest that Palaeoproterozoic crust underlies both the Main Range and Eastern Province granites. Our εHf model age of ca. 1750 Ma from Sibumasu, the basement underlying eastern Myanmar, lies within the range of other model ages reported thus far for the Baoshan Block north in Yunnan, interpreted by some to be the northern extension of Sibumasu.